Beyond haemostasis: Crosstalk between human platelets and multiple myeloma cells - Kulkarni, Anushka (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2026)
Multiple myeloma (MM) is a haematological malignancy characterised by unhindered proliferation of plasma cells. It is well established that cancer cells can aggregate platelets, a phenomenon known as tumour cell induced platelet aggregation (TCIPA). TCIPA correlates with tumour progression in solid tumours, but little is known about its role in haematological malignancies, in particular MM. The overall aim of this thesis is to investigate the multifaceted mechanisms of myeloma-human blood platelet crosstalk, integrating platelet aggregation assays, proteomics, invasion and migration assays, and PI-based cell death assays to determine how platelets influence MM cell behaviour, proteomic adaptation, and the therapeutic response to bortezomib. For this purpose, washed platelets were prepared from whole blood obtained from healthy volunteers and exposed to MM cell lines (MM.1S, JJN-3, KMS-27 and U266) under specific experimental conditions. Results from light transmission aggregometry (LTA) demonstrated that MM cells induce platelet aggregation in a cell line-dependent manner. MM.1S and KMS-27 cells consistently induced platelet aggregation, whereas JJN-3 and U266 did not, highlighting intrinsic heterogeneity in platelet responsiveness to each cell line. Pharmacological modulation indicated that TCIPA involves distinct combinations of ADP-, TXA-, and MMP-dependent pathways, varying by cell type. Differences in platelet aggregation under quasi-static (LTA) versus static (ultrasound standing wave trap) conditions further revealed that effective platelet activation may depend upon direct, sustained MMplatelet contact, with tumour cell number affecting the platelet response. Proteomic profiling across MM.1S, KMS 27, JJN 3, and U266 cell lines showed that platelets interaction with those cell lines profoundly remodels the myeloma secretome, reshaping pathways linked to metabolism, cytoskeletal organisation, and proteostasis. Enrichment of metabolic enzymes (e.g., G6PD, ENO1), adhesion molecules (VINC, TLN1, GELS), and stress response proteins (HSP90, HSPB1) revealed platelet-induced metabolic reprogramming and activation of adhesion-mediated survival signalling. Few of the proteins were found to be strongly associated with drug resistance and myeloma progression after a literature search. A conserved signature of 14 proteins across all the MM cell lines, included CAP1, ARRB1, CALM, and COTL1, impliying an adaptive response promoting proliferation, immune modulation, and therapy resistance. Based on results of proteomics, invasion and migration assays were performed. These assays showed that MM cell-platelet co culture alters MM motility and invasion in a context dependent manner. While the co-incubation of platelets induced an increased MMP 2 and MMP 9 activity, they restricted invasion in matrix-based assays. The most clinically relevant finding was that co-incubation significantly increased the migratory capacity of MM.1S and U266 cells, with comparable donor-dependent responses observed in KMS 27 and JJN 3. The use of platelets or platelet releasate as chemoattractants reduced cell migration, except in MM.1S cells. These findings indicate that physical platelet-cell interactions maybe the principal drivers of MM cell motility, underscoring important mechanistic differences from adherent solid tumour models. Further studies are required to investigate the role of MM cell-platelet releasate co-incubation in migration of MM cells. Finally, analysis of proteasome inhibitor sensitivity indicated that platelet association may reduce bortezomib-induced cytotoxicity, though technical constraints prevented definitive quantification. Further experiments using cells secretome suggested that protection against bortezomib involves contact dependent, not entirely through soluble factors, if there are any. Collectively, this work demonstrates that MM cells can aggregate platelets in vitro and that platelets, in turn, modulate the myeloma microenvironment. Further studies are necessary to validate the exact molecular pathways involved during this process.
APPROVED
Keywords: Platelets; Migration; Proteomics; Drug modulation; TCIPA; multiple myeloma